KORELASI KADAR HEMOGLOBIN DENGAN KUALITAS HIDUP PADA USIA LANJUT DI PANTI WERDHA PROVINSI DIY - , HERMAWAN, Dr. Johan Kurnianda, SpPD-KHOM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Anemia is a condition often encountered in the elderly, with prevalence estimation ranging from 9-18% in men and 8-13% in women and increased to 20% at age above 85 years. The cause of anemia in the elderly associated with bleeding or nutritional deficiency, chronic disease and an unknown cause. Anemia is an independent predictor of adverse outcomes for the elderly. Symptoms are frequent in patients complaining of anemia is directly related to fatigue, namely subjective sensation of weakness, loss of energy and fatigue, both physical, emotional, cognitive, and will affect the quality of life of elderly patients. Quality of life is the sum of ability, disability, complaints and feelings of that occurs as a result of illness, treatment or medical intervention. The purpose of this study was to determine the correlation between hemoglobin levels with quality of life in the elderly who live in Panti Werdha. Research using cross-sectional research design in the elderly in Panti Werdha Province of Yogyakarta. Research time was conducted in November 2010. Elderly people who meet inclusion and exclusion criteria, underwent physical examination, routine blood tests and assessment of quality of life using short-form-36 direct interview. Statistical test was done with Pearson correlation for normal data and Spearman's correlation when the data is not normal. Differences considered significant if p <0.05 with 95% confidence interval. The results present the characteristics of study subjects by age, sex, educational level, BMI, and comorbid disease. Categorical data are presented in percentages and numeric data in mean and standard deviation. This study shows the correlation between hemoglobin levels with quality of life of elderly in Panti Werdha, DIY.